ECOLOGICAL AND TECHNOLOGICAL REGULARITIES OF SALT BRINES FORMATIONS OF DOMBROVSKY QUARRY - Malkova, Y.; Yakovlev, Y.; Dolin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Dombrovsky quarry, which has been in operation since 1967, is the only one in the world where potash ore has been mined by open-pit method. The article considers the body formation mechanism of water-salt brines in the Dombrovsky quarry and gives a brief overview of the problems due to long-term development of the Kalush-Golynsky potassium salts deposit and waste accumulation in the area of hydraulic geofiltration. Such problems include flooding of the Dombrovsky salt quarry, erosion of salt dumps by precipitation, tailings overflows, pollution of the Quaternary supersalt aquifer and significant water quality deterioration danger in urban water intake, development of salt karst and subsidence of the earth’s surface, destruction of engineering structures, residential buildings, etc. Analytical data of water inflows dynamics into the quarry and the increase of the drainage area of the quarry riparian part was analyzed, accompanied by drainage of the circular drainage trench – separation of groundwater level from the bed, the karst formation development on the periphery of the quarry (up to 250–350 m and more), anomalous increase in clay-dust fractions in the quarry wastewater after the flooding 2008 with a simultaneous increase in water inflows. According to the research, we can make a conclusion about the unloading of liquid body filling the quarry in the thickness of the pebble supersalt aquifer, filling karst cavities, erosion of the quarry, increasing the volume of the quarry bowl and the size of the groundwater drainage area of alluvial gravel-sand deposits of Sivka and Lymnutsya. Based on the obtained results, a conclusion was made regarding the threat of the emergency situation development and the deterioration of life safety in areas with disturbed ecological parameters of the geological environment. There is a need for artificial adjustment of the environmental forecast ecological parameters according to monitoring observations.